Application of Remote sensing and GIS technologies for study of seasonal snow cover in Georgia - Lomidze, N.; Janjalia, T.; Koridze, K.; Tvauri, G.; Zilpimiani, D. (Journals of Georgian Geophysical Society, 2015)
Terra MODIS Snow product were used for seasonal snow cover study in Georgia. Spatial and temporal distribution data of snow covered areas in 2012 January-December period were obtained for 12 regions of Georgia. Preliminary results of snow cover dynamics were obtained. Investigation of seasonal snow cover dynamics for 2000-2014 time periods is underway. Seasonal snow cover is an important component of climate system significant part – cryosphere. It effects on climate, relief, hydrographic and soil formation processes, plant and animal living ecosystem. The practical significance of snow cover is determined by the hydrographic network formation, development of mountain tourism, transport functioning in winter period. Snow cover influence on climate is determined by interaction with atmosphere. Duration of seasonal snow cover duration is conditioned by winter temperatures, which in its turn, during the last decades, experiences changes with the tendency of warming and is expressed by the significant decrease of seasonal snow cover in north hemisphere. Together with natural factors, this process is emphasized also by anthropogenic factors. Snow cover area change impacts on climate, ecosystems and population welfare both in global and regional scale.